Kinematics of steep bedrock permafrost - Hasler, Andreas; Gruber, Stephan; Beutel, Jan; id_orcid:0 000-0003-0879-2455 (Journal of Geophysical Research: Earth Surface, 2012)
ISSN:0148-0227 ISSN:2169-9003 ISSN:2169-9011